Prehospital Ketamine Use in Pediatrics. (3rd April 2023) - Goyal, Ashima; Frawley, John; Gappy, Revelle; Sandoval, Sariely; Chen, Nai-Wei; Crowe, Remle; Swor, Robert
Abstract: Introduction: Information regarding prehospital ketamine use in the pediatric population is limited as existing literature focuses primarily on critical care and air transport. Our objective was to describe patient characteristics among pediatric EMS patients who received ketamine. Secondarily, we assessed effectiveness, deviation from recommended dosing, and adverse outcomes of pediatric EMS patients who received ketamine. Methods: We conducted a retrospective data review of records from the ESO Data Collaborative for all 9-1-1 transports of pediatric patients (≤ 18 years of age) who received ketamine from 2019-2020. We categorized EMS primary impressions as a proxy for medication indication. We defined effectiveness as paramedic-identified clinical improvement, and pain relief as decrease in pain score ≥2 points between initial and final recording. Descriptive statistics were used to summarize clinical characteristics. Non-parametric Wilcoxon signed-rank test was used to assess change in pain score. Results: Out of 422, 968 ground-ambulance pediatric patients, 1, 291 received ketamine. They were predominately male (842, 65.2%), teenagers (median age 16, IQR: 13-17), Caucasian (810, 62.7%), and from urban areas (1, 041, 80.6%). The most common EMS impressions were related to injuries (810, 62.7%) and behavior disorders (281, 21.8%). Only 980/1, 291 (75.9%) had weights and identifiable routes recorded. Most patients (960, 74.4%) received single doses of ketamine, with EMS clinicians reporting improvement in 855 (89.1%) of 960 patients. Among non-behavioral emergency patients, 727/1, 010 (72.0%) had pain scores recorded. Pain scores decreased significantly from a median of 8 (IQR: 4-10) to 2 (IQR: 0-6) (p < 0.001) with 59% (429) of 727 patients reporting pain score reductions of 2 or more points. Desaturation (<90% SpO2 ) events were noted to be minimal (1.8%). A small number (28, 2.2%) received positive pressure ventilation without advanced airway placement. No prehospital deaths were documented. Conclusion: In this large review of pediatric prehospital ketamine use, ketamine was primarily used for analgesia, but was frequently used for other indications. Most patients were observed to improve after ketamine use, with most injured patients reporting decreases in pain scores. We observed few significant adverse events related to ketamine use in this population.